2016
DOI: 10.3390/f7110282
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nitrogen Pools and Fluxes in Adjacent Mature Norway Spruce and European Beech Forests

Abstract: Abstract:We compared two adjacent mature forest ecosystem types (spruce vs. beech) to unravel the fate of assimilated carbon (C) and the cycling of organic and inorganic nitrogen (N) without the risk of the confounding influences of climatic and site differences when comparing different sites. The stock of C in biomass was higher (258 t·ha −1 ) in the older (150 years) beech stand compared to the younger (80 years) planted spruce stand (192 t·ha −1 ), whereas N biomass pools were comparable (1450 kg·ha −1 ). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 66 publications
1
4
1
Order By: Relevance
“…The measured respiration decline of 6% -10% under S treatment is similar to that found in a recent meta-analysis (7%) based on experiments from China (Feng et al, 2017). The reduction of CO2 effluxes under S treatment corresponds to the 27% -49% of annual litter production (aboveground litterfall of 1937 kg C ha -1 year -1 between 2013-2016, Oulehle et al, 2016b). Based on a total S addition of 50 kg S ha -1 year -1 this corresponds to the suppression of decomposition by 10.6 to 19 kg C kg S -1 .…”
Section: Acidification Effects On Soil Carbon Dynamicssupporting
confidence: 85%
See 3 more Smart Citations
“…The measured respiration decline of 6% -10% under S treatment is similar to that found in a recent meta-analysis (7%) based on experiments from China (Feng et al, 2017). The reduction of CO2 effluxes under S treatment corresponds to the 27% -49% of annual litter production (aboveground litterfall of 1937 kg C ha -1 year -1 between 2013-2016, Oulehle et al, 2016b). Based on a total S addition of 50 kg S ha -1 year -1 this corresponds to the suppression of decomposition by 10.6 to 19 kg C kg S -1 .…”
Section: Acidification Effects On Soil Carbon Dynamicssupporting
confidence: 85%
“…and mature European beech forest (Fagus sylvatica L.). The spruce stand consists of Norway spruce monoculture planted in the early 1930s, and the beech stand consists of European beech monoculture (Oulehle et al, 2016b). The distance between stands is approximately 1 km and both stands are underlined by gneiss bedrock.…”
Section: Sites and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Iost et al [14] reported an exceedance of critical limits in DIN (N- ). This stands in contrast to studies reporting higher N leaching under spruce [38,42] as a result of higher deposition of N. However, a comparison of the C/N ratio of the two organic horizons [25] revealed a lower C/N ratio in the FH horizon under beech (beech stand: 19.9 vs. spruce stand: 23.3). According to Gundersen et al [51], when the C/N ratio is less than or equal to 25, there is a high probability that leaching will occur.…”
Section: N Budgetcontrasting
confidence: 96%